KRISIS BUDAYA ORGANISASI DALAM PELAYANAN PUBLIK DIGITAL - Nayla Mi'raz Salsabila; Keisya Hilda Adzania; Dwi Yuliani; Ahmad Raihan Habiburrahman; Zaki Anandya Putra (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
A well-functioning organization is one that consistently adopts positive habits, allowing them to evolve into an adaptive and service-oriented work culture. However, in the context of digital public services in Indonesia, there are still organizations that maintain poor habits to the extent that they develop into a cultural crisis. This study aims to analyze the forms of organizational culture crisis in the implementation of digital public services through the Digital Population Identity (IKD) application, as well as to identify the factors that hinder its effectiveness. This research employs a descriptive qualitative approach, with data collection techniques conducted through a literature review, supported by an analysis of public reviews on the Google Play Store platform as empirical evidence of service conditions. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the organizational culture crisis in the implementation of IKD is manifested in four forms. The inhibiting factors, as well as their impacts, include a decline in the quality of digital services, the obstruction of the bureaucratic reform agenda, and an increased burden on the public. This study emphasizes that the success of digital transformation in public services cannot be achieved without a systemic, adaptive, and sustainable transformation of organizational culture.